PENGARUH MODEL KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP MOTIVASI BELAJAR SISWA KELAS IV DI SD NEGERI 060841 MEDAN - Waruwu, Yolanda Aristina; Juliana; Ester Julinda Simarmata; Eka Margaretha Sinaga; Irmina Pinem; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the cooperative learning model of the Student Achievement Division (STAD) type on the learning motivation of fourth-grade students at SD Negeri 060841 Medan Petisah in the 2024/2025 academic year. This research employed a quantitative approach. The population of the study consisted of all students from grades I to VI at SD Negeri 060841 Medan Petisah, totaling 174 students. The sample was selected using a purposive sampling technique, with 23 fourth-grade students serving as the research sample. The results of the study indicated a correlation coefficient of 0.669, meaning that rcalculated ​ (0.669) ≥ rtable ​ (0.433); therefore, the alternative hypothesis (Ha) was accepted. This result shows a very strong effect of the cooperative learning model of the Student Achievement Division (STAD) type on the learning motivation of fourth-grade students at SD Negeri 060841 Medan Petisah. Furthermore, the t-test results showed that tcalculated ​ ≥ ttable ​, namely 4.120 ≥ 2.069, confirming that Ha was accepted. Thus, it can be concluded that there is a positive and significant effect of the cooperative learning model of the Student Achievement Division (STAD) type on the learning motivation of fourth-grade students at SD Negeri 060841 Medan Petisah in the 2024/2025 academic year.